Persistent high macrolide resistance rate and increase of macrolide-resistant ST14 strains among Mycoplasma pneumoniae in South Korea, 2019–2020 - Joon Kee Lee; Youn Young Choi; Young Joo Sohn; Kyung-Min Kim; Ye Kyung Kim; Mi Seon Han; Ji Young Park; Eun Young Cho; Jae Hong Choi; Eun Hwa Choi (Journal of Microbiology, Immunology and Infection, 2022)
Background: Expansion of the single sequence type 3 (ST3) was associated with a high macrolide resistance rate among Mycoplasma pneumoniae in Korea during the 2014–2016 epidemic. This study investigates the macrolide resistance rate and genetic diversity of the subsequent epidemic of M. pneumoniae pneumonia in 2019–2020. Methods: The culture for M. pneumoniae was developed from 1228 respiratory samples collected from children with pneumonia in four hospitals in Korea between January 2019 and January 2020. Determination of macrolide resistance and multilocus sequence typing analysis were performed on M. pneumoniae isolates. eBURST analysis was applied to estimate the relationships among strains and to assign strains to a clonal complex. Results: M. pneumoniae was cultured in 93 (7.6%) of 1228 clinical samples. The overall macrolide resistance rate of M. pneumoniae strains was 78.5% (73/93). Of the nine STs identified, three were novel. The most common ST was ST3 (66 [71.0%]) followed by ST14 (18 [19.4%]) and ST7/ST15 (2 [2.2%] each). Three STs (ST3, ST14, and ST17) exhibited macrolide resistance. The macrolide resistance rates of ST3 and ST14 were 98.5% (65 of 66) and 38.9% (7 of 18), respectively. Conclusion: Compared to the previous outbreak in 2014–2016, the overall macrolide resistance remained high; however, an increasing proportion of macrolide resistance was observed within ST14 strains in 2019–2020.